Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 6 - Test: 26

Answer

$x_{1}=1$ and $x_{2}=-\dfrac{2}{3}$

Work Step by Step

$(x-1)(3x^2-x-2)=0$ $(x-1)(3x^2-3x+2x-2)=0$ $(x-1)[3x(x-1)+2(x-1)]=0$ $(x-1)(x-1)(3x+2)=0$ $(x-1)^2(3x+2)=0$ Therefore the solutions are $x_{1}=1$ and $x_{2}=-\dfrac{2}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.